LEGAL PROTECTION OF WOMEN VICTIMS OF DOMESTIC PSYCHICAL VIOLENCE Case Study Decision Number 298/Pid.Sus/PN Mdn - Ramadhan, Bagas (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
Crimes of violence in the domestic sphere still often occur due to a mistaken understanding of gender bias, where a woman must submit to a man. Gender bias also pressures women to be submissive and accept all forms of unfair behavior. In general, gender bias also places women in a weak position, thus making men more dominant in the family system and society, this is very detrimental to women, so that women are more often experience violence. Domestic violence is often called hidden crimehidden). The type of research for this thesis is normative legal research with a descriptive research nature, while the data collection method is library study, using secondary data consisting of primary, secondary and tertiary legal materials and using qualitative data analysis. Imposing criminal sanctions on the defendant must also take into account the proportionate losses experienced by the victim. The panel of judges in the aquo case should have informed the victim regarding Article 98 of the Criminal Procedure Code which states that if an act which is the basis of an indictment in a criminal case examination by a district court causes harm to another person, then the presiding judge at the hearing's request may decide to consolidate the case. claim for compensation in criminal cases. The judge in a trial related to a criminal offense where the victim is a woman should inform the victim regarding Article 98 of the Criminal Procedure Code and then the notification statement to the victim regarding Article 98 of the Criminal Procedure Code must be recorded in the decision.